Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve the equation for x. 16(x - 3) = 13(x + 2)
Explain Concept Rules


Sagot :

Answer:

Step-by-step explanation:

Let's solve your equation step-by-step.

16(x−3)=13(x+2)

Step 1: Simplify both sides of the equation.

16(x−3)=13(x+2)

(16)(x)+(16)(−3)=(13)(x)+(13)(2)(Distribute)

16x+−48=13x+26

16x−48=13x+26

Step 2: Subtract 13x from both sides.

16x−48−13x=13x+26−13x

3x−48=26

Step 3: Add 48 to both sides.

3x−48+48=26+48

3x=74

Step 4: Divide both sides by 3.

3x/3 =74/3

x = 74/3

Answer:

x= 74/3